TINDAK PIDANA PENCEMARAN NAMA BAIK MELALUI MEDIA ONLINE DITINJAU DARI UNDANG-UNDANG INFORMASI TRANSAKSI ELEKTRONIK - Syarifudin, syarifudin (Universitas Prof. Dr. Hazairin, SH, 2021)
One of the abuses of the internet is defamation by someone against another party. Things or circumstances that are communicated or published via the internet can be said to be insults or defamation if the things or conditions are not true for the victim, whether it is something that damages the reputation or brings material loss to the victim. In this study, the type of approach that will be used is the statute approach, which is an approach that is carried out by reviewing all laws and regulations related to defamation which is carried out online. In the ITE Law, criminal acts of defamation are expressly regulated in Article 27 paragraph (3) of the ITE Law in which violations of Article 27 will be punished with imprisonment for a maximum of 6 (six) years and/or a fine of a maximum of Rp. 1,000,000,000. ,00.